Anti-HBs persistence and anamnestic response among medical interns vaccinated in infancy - Nesrine Fathi Hanafi; Nashwa Naguib Omar; Ghada Abdelwahed Ismail; Amani Ali El-Kholy; Ahmed ElShafei; Sara AbdelAziz Essa (Scientific Reports)
Abstract Medical interns are at high risk of acquiring Hepatitis B Virus (HBV) infection during their training. HBV vaccination is the most effective measure to reduce the global incidence of HBV. The duration of protection after HBV vaccination is still controversial. We aimed to determine the prevalence of protective anti-HBs levels among medical interns who had received compulsory hepatitis B vaccination in infancy, and to assess the anamnestic response of those subjects with non-protective antibodies titers, to a booster dose of the vaccine. We conducted a cross-sectional study on 519 medical interns in 2022. We examined their immunization status and records. Blood samples were collected and qualitative testing of Hepatitis B surface antigen (HBsAg), and quantitative testing of Hepatitis B surface antibody (anti-HBs) were performed. For medical interns whose titers were ˂ 10 mIU/mL, a booster dose of the vaccine was given, followed by repeat testing of anti-HBs 2 months later. About 304 (58.6%) of the medical interns revealed titers higher than or equal 10 mIU/mL. About (44.93%) of male medical interns showed an immunity level below 10 mIU/mL. However, (43.91%) of female medical interns had an antibody titer of 100 mIU/mL or higher. All subjects who got a booster dose presented a titer level of 10 mIU/mL 2 months later. About (41.4%) of our medical interns enrolled in the study had anti-HBs titer ˂ 10 mIU/mL. This raises the importance of establishing a screening protocol and offering booster dose for those at risk to protect them against the high risk of infection.